Encyclopedia of Gender and Information Technology 2006
DOI: 10.4018/978-1-59140-815-4.ch044
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Girls' Choice of Information Technology Careers

Abstract: Many western nations have experienced declining numbers of women in the information technology (IT) workforce (Trauth, Nielsen, & von Hellens, 2003). Between 1996 and 2002, women in the U.S. IT workforce declined from 41% to 34.9% (ITAA, 2003). This can hamper diversity and reduce the talent pool that can address needs of diverse end-users (Florida & Gates, 2002). Why do women choose IT careers or reject them? Multidisciplinary research on career genderization reveals gender imbalance (Trauth, Nielsen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Based on a search of relevant literature and an empirical study, a model of Girls' ICT Study and Career Choices (see Figure 1) was developed. The model captures the many factors that influence Australian girls' ICT study and career choices and uses similar groupings to those suggested in Adya and Kaiser's (2006) seminal paper. However, Clayton's research indicated other influential factors that were not included in the early determinants of Adya and Kaiser, such as socio‐economic status involving family and ICT access issues.…”
Section: The Model Of Girls' Ict Study and Career Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a search of relevant literature and an empirical study, a model of Girls' ICT Study and Career Choices (see Figure 1) was developed. The model captures the many factors that influence Australian girls' ICT study and career choices and uses similar groupings to those suggested in Adya and Kaiser's (2006) seminal paper. However, Clayton's research indicated other influential factors that were not included in the early determinants of Adya and Kaiser, such as socio‐economic status involving family and ICT access issues.…”
Section: The Model Of Girls' Ict Study and Career Choicesmentioning
confidence: 99%
“…According to Adya & Kaiser (2006), early parental involvement in a child's career planning has been found to have a clear positive bearing on the choice of ICT as a career. Furthermore, Dryler (1998) stated that children often make vocational and occupational choices in the same area as their parents and that highly educated parents promoted gender‐atypical occupations more than less educated, or working‐class, parents.…”
Section: Evaluation Of the Programmementioning
confidence: 99%
“…They showed that mentoring can serve as an important intervention to enhance the retention of women in the ICT workforce because of its correlation with professional advancement. Several studies (Nielsen et al ., 1997; Adya & Kaiser, 2005; 2006; Adya, 2008; Soe & Yakura, 2008) have addressed the topic of varied cultural influences in analyses of gender and IT. The individual differences theory of gender and IT has been developed to provide a theoretical lens that focuses explicit attention on with‐gender rather than between‐gender variation in the ways that individuals are exposed to, experience and respond to gender relations in the ICT profession (Trauth & Quesenberry, 2006).…”
Section: Maturing Of the Research Area: Methods Theory Focusmentioning
confidence: 99%
“…Clayton, Beekhuyzen and Nielsen's article theorised the effectiveness of interventions with school‐aged females. Using a substantial doctoral study, which further developed Adya and Kaiser's (2005; 2006) model of young women's career choice influences, this article examines the effectiveness of a 1‐day action for girls, a popular type of intervention. The paper takes into account the difficulty of undertaking research into interventions, when the conduct of the experience may be affected by contextual facts.…”
Section: Articles Included In the Special Issuementioning
confidence: 99%
“…BT alanının eğitimine ve mesleklerine yönelik ilginin azalmasında; cinsiyet, ırk (etnik yapı) ve milliyet gibi üç ana etmenin etkileri (Singh, ve diğerleri, 2007), yaşanılan coğrafya ve ekonomik nedenler ile BT alanında çalışan kadın örneklerin azlığı (Trauth, 2006;akt. Miliszewska ve Sztendur, 2010;Von Hellens ve diğerleri, 2009) yanında kültür (Adya ve Kaiser, 2006), toplumun yapısı ve bireysel etmenler önemli rol oynamaktadır (Trauth, Quesenberry, ve Morgan, 2004). Ayrıca politik nedenler ya da hükümet politikaları ve ailenin meslek seçimi sürecindeki rolü de BT sektörüne katılacak kadınların karşılaşacakları engeller arasında sayılmaktadır (Georgiadou, ve diğerleri, 2009).…”
Section: Cinsiyetunclassified